Pengaruh Disiplin Kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan pada UD. Karya Pala Kediri - Imanda Mafesa Milania; Rike Kusuma Wardhani; Nuril Aulia Munawaroh (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
This study aims to determine the effect between work discipline (X1) and work environment (X2) variables on employee performance (Y) at UD Karya Pala Kediri. This type of research is quantitative research. The data collection techniques used are primary data and secondary data. Sample selection using saturated sampling method, the number of samples in the study obtained as many as 34 respondents at UD Karya Pala Kediri. This research data was obtained through questionnaires, interviews, and literature studies. The analysis techniques used are Validity Test, Reliability Test, Classical Assumption Test, Multiple linear regression analysis, t test, F test and Determination coefficient test. The results obtained multiple linear regression equation Y = 11.312 + 0.365X1 + 0.603X2 and the results of the t test variable work discipline and work environment partially significant effect on employee performance. The F test results obtained Fcount results with a significance value of 0.000 <0.05. From the results of the analysis it can be concluded that work discipline and work environment simultaneously and significantly affect employee performance.